The influence of perspective on VR job interview training - Ueda, Fumitaka; Fujimoto, Yuichiro; Sawabe, Taishi; Kanbara, Masayuki; Kato, Hirokazu (Frontiers in Virtual Reality, 2024)
Third-person perspectives in virtual reality (VR) based public speaking training enable trainees to objectively observe themselves through self-avatars, potentially enhancing their public speaking skills. Taking a job interview as a case study, this study investigates the influence of perspective on the training effects in VR public speaking training and explores the relationship between training effects and the sense of embodiment (SoE) and presence, as these concepts are central to virtual experiences. In the experiment, VR job interview training was conducted under three conditions: a first-person perspective (1PP), a typical third-person perspective from behind the avatar (Back), and a third-person perspective from the front of the avatar (Front). The results indicate that participants trained in the Front condition received higher evaluations from others in terms of verbal communication skills and the overall impression of the interview compared to those trained in the other conditions, highlighting the advantages of training while observing a self-avatar. Furthermore, it was confirmed that training effects correlated with the subcomponents of SoE and presence, suggesting that these trends may vary depending on perspective.